Aplicación Web para la automatización del cobro de consumo de agua potable en el Gobierno Autónomo Descentralizado Rural de la Parroquia Milagro del Cantón Atahualpa - Sanmartín Freire, Edhisson Alexis (2023)
One of the main advantages or privileges offered by technology and the modern world is automation, which helps to optimize each of the processes of the organizations. These parameters are of vital importance to save time, money and human effort in the realization of constant tasks. Regarding this, the main objective of this titling work is to develop a web platform as a service for the automation of drinking water consumption collection in the parroquia Milagro del cantón Atahualpa, in order to answer the following research question: What Is it important to propose a web application to automate the collection of drinking water consumption in the Rural Decentralized Autonomous Government of the Parroquia Milagro del Cantón Atahualpa? This Degree Work consisted of three phases, in the first phase the interview technique was applied to obtain requirements of the web application, obtaining the requirements specification document according to the IEEE 830 standard. Likewise, the design of each of the technological artifacts of the application was carried out with the help of the XP software development methodology and using the 4 + 1 architectural model that is based on thes views of scenarios, logic, physics, deployment and processes with the diagrams of use cases, classes, deployment, components and activity respectively to each of them to have a better organization of the project. In the second phase the web application was developed through the model view controller that brings by default Django and therefore in this same Framework with the help of PostgreSQL as a Database, coding functionalities such as customer income of the service, entry of figures consumed by customers, record of service charges, Notifications to customer emails for outstanding debts of the service, among other functionalities. Finally, as a last phase, the acceptance test of the web application was carried out with the client, which was based on conducting an interview where the application is validated taking as reference the requirements of the same and on the other hand the usability of the software. Similarly, the recoding of the application was based on better developing some of the functionalities that did not completely meet the client's expectations, in this case, implementing login password recovery. Likewise, the unit tests determined that the software models work correctly; Thanks to the load and stress tests, it was defined that the application has a minimum number of failures and has optimal response times between the client and the server. keywords: Software Development, Web Applications, Django Framework, Water Service.